Preparation method and application of bio-based phytate efficient charring agent
By grafting phytic acid at multi-coordinated sites on the lignin substrate, combining multi-element synergistic effect and lewis acid catalysis, the high carbonization rate of vegetation is achieved, solving the shortcomings of traditional barrier belt construction, and improving fire protection efficiency and Environmental protection.
Patent Information
- Application Number
- CN202510012532.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2045-01-06
AI Technical Summary
In the prevention and control of forest and grassland fires, traditional barrier belt construction projects are large, high in cost and poor in emergency, making it difficult to quickly and efficiently suppress the spread of fires. At the same time, water-soluble and foam fire extinguishing agents have problems of low efficiency and ecological disadvantage.
The phytic acid at multiple coordination sites is grafted on the lignin substrate through the phosphate esterification reaction, providing the anchor positioning point of the metal and regulating the coordination microenvironment, thereby improving the catalytic carbonization effect of the charcoal-forming agent. Phytic acid provides a high coordination environment for metals, and at the same time, coupling the multi-lewis sites of phytic acid itself and the multi-element flame retardant synergistic effect, achieving high carbon yield in vegetation.
It has achieved high carbonization rate in vegetation, improved the fire protection efficiency, timeliness and environmental protection of the fire protection system, and has good flame suppression and smoke suppression performance.
Smart Images

Figure CN119431822A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of forest and grassland fire prevention and control and flame retardancy, and in particular relates to a preparation method and application of a bio-based phytate high-efficiency carbonizing agent. Background Art
[0002] The frequent occurrence of forest and grassland fires caused by the intensification of climate change has caused immeasurable losses to human life and property safety. The construction of fire barriers is an important measure to control the development of sudden forest and grassland fires. However, the construction of traditional barriers such as mechanized farming, burning and biological fire prevention forests is large in construction volume, high in cost and poor in emergency response, making it difficult to quickly and efficiently suppress the spread of fires. Therefore, the construction of efficient emergency fire barriers is an important development need for the precise prevention and control of forest and grassland fires in my country.
[0003] At present, emergency disposal methods such as placing water-soluble fire extinguishing agents and foam fire extinguishing agents in the burning area and downwind area are often used in forest and grassland fires at home and abroad. They are used to quickly extinguish the flames while accumulating on the surface of vegetation to form a fire barrier. The water-soluble fire retardants currently used are mainly diammonium hydrogen phosphate, ammonium sulfate, and oligoammonium phosphate. They rely on their own cracking to produce a certain fire retardant effect, which is inefficient; and although foam fire extinguishing agents can effectively adhere to the surface of vegetation and isolate the air, the accumulation of a large number of harmful components is not conducive to ecological balance. Therefore, the development of bio-based catalytic carbonization fire retardants, by catalyzing the dehydration and carbonization of cellulose, hemicellulose, etc. in vegetation, forms a dense carbonization layer to isolate the air and inhibit the thermal decomposition of the inner layer, strengthens the interaction between fire retardants and vegetation to form efficient carbonization, and is expected to improve the fire prevention efficiency, timeliness and environmental protection of the fire prevention system. Summary of the invention
[0004] In view of the problems existing in the above-mentioned prior art, the present invention provides a method for preparing a bio-based phytate efficient carbonizing agent and its application. The present invention grafts phytic acid with multiple coordination sites on a lignin substrate through a phosphatization reaction, provides anchoring sites for metals and regulates the coordination microenvironment, thereby improving the catalytic carbonization effect of the carbonizing agent. In addition, the multiple elements N and P and the rich Lewis acid active sites provide different carbonization synergistic mechanisms, further enhancing the carbonization effect. The present invention utilizes phytic acid to provide a high coordination environment for metals, while coupling the multiple Lewis sites of phytic acid itself and the multi-element flame retardant synergistic effect, thereby achieving a high carbonization rate of vegetation, which can be used to construct emergency fire barrier zones.
[0005] The preparation method of the bio-based phytate high-efficiency carbon-forming agent of the present invention comprises the following steps:
[0006] Step 1: Disperse lignin in a solvent, add phytic acid after stirring for 30 minutes, then add urea as a reaction catalyst, heat to reflux for esterification reaction; after the reaction is completed, centrifuge and wash the product to remove unreacted products, and dry to obtain phytic acid-modified phospholipid lignin.
[0007] Step 2: The phytic acid-modified phospholipid lignin obtained in step 1 is dispersed in a solvent, a copper salt aqueous solution is added dropwise under heating, magnetic stirring is performed, and centrifugal washing is performed to obtain a bio-based phytate high-efficiency carbonizing agent.
[0008] In step 1, the mass ratio of lignin to phytic acid is 2:3-4, and urea accounts for 10-25wt% of lignin.
[0009] The phytic acid is added in the form of a phytic acid aqueous solution, and the concentration of the phytic acid aqueous solution is 50%. The mass ratio of lignin to phytic acid is based on the mass of the phytic acid solution.
[0010] The lignin is dealkalized lignin.
[0011] In step 1, the heating reaction temperature is 70° C. and the reaction time is 8 h.
[0012] In step 1, the solvent is tetrahydrofuran.
[0013] In step 2, the copper salt is copper acetate.
[0014] In step 2, the mass ratio of phospholipid lignin modified with phytic acid to copper salt is 1:0.025-0.25, preferably 1:0.05. If the ratio of copper salt is too high, the excess Cu will catalyze degradation at a faster rate, the matrix will be severely damaged, and it will be difficult to form a stable carbon layer.
[0015] In step 2, the heating temperature is 50° C. and the reaction time is 2 h.
[0016] In step 2, the solvent is deionized water.
[0017] The invention discloses an application of the bio-based phytate high-efficiency carbon-forming agent in constructing a fire barrier belt.
[0018] Specifically, the bio-based phytate high-efficiency charring agent is added to the vegetation firebreak and used in combination with ammonium polyphosphate (acid source, gas source) to promote the charring of the vegetation itself and improve the flame retardant performance and flame suppression effect.
[0019] The vegetation firebreak includes coniferous vegetation such as Masson pine, Armand pine, Platycladus orientalis, Metasequoia glyptostroboides and broad-leaved vegetation such as Mongolian oak, white birch, Ginkgo biloba and trees.
[0020] The mass ratio of the carbon-forming agent to ammonium polyphosphate is 1:1-7.
[0021] The spraying amount should be at least 100g / m 2 .
[0022] The present invention grafts phytic acid onto the surface of lignin through an esterification reaction, and combines the synergistic effect of P and N multi-elements and the catalytic carbonization effect of Lewis acid by coordinating and loading copper ions, thereby achieving a significant fireproof carbonization effect. While the metal ions coordinate with phytic acid, they also coordinate with the hydroxyl groups on lignin. In this multi-coordination environment, the oxidation state shift of Cu is more obvious, which is conducive to improving the catalytic carbonization effect.
[0023] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0024] 1. Compared with the traditional fire retardant for forest and grassland fire, the present invention has good flame suppression ability and high carbonization effect after compounding with APP.
[0025] 2. The preparation method of the carbon-forming agent of the present invention is simple and easy to operate.
[0026] 3. The metal-modified phytic acid-based carbon-forming agent of the present invention couples multi-element synergy, multi-active sites and the like, which is beneficial to promoting the carbonization of vegetation itself. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.
[0028] Figure 1 The scanning electron microscope images of the sample prepared in Example 1 of the present invention and the comparative sample are shown.
[0029] Figure 2 Thermogravimetric analysis curves of the sample prepared in Example 1 of the present invention and the comparative sample.
[0030] Figure 3 A heat release rate diagram of the materials is provided for Examples 2-5 of the present invention and the comparative examples.
[0031] Figure 4 A total heat release rate graph of the materials is provided for Examples 2-5 of the present invention and the comparative examples.
[0032] Figure 5 A total smoke release rate graph of the materials is provided for Examples 2-5 of the present invention and Comparative Examples.
[0033] Figure 6 This is the temperature curve of fire spread of pure pine needles.
[0034] Figure 7 This is a temperature curve diagram of the fire spread experiment set up in Example 6 of the present invention.
[0035] Figure 8 This is a temperature curve diagram of the fire spread experiment set up in Example 7 of the present invention.
[0036] Fig. 9 This is a temperature curve diagram of the fire spread experiment set up in Example 8 of the present invention.
[0037] Fig.10 It is a thermogravimetric curve diagram under air after ammonium polyphosphate and a carbon-forming agent are compounded in different proportions and added in an amount of 10% of the mass of pine needles in an example of the present invention.
[0038] Fig.11 For example of the present invention Fig.10 A partial enlarged view of .
[0039] Fig.12 This is the thermogravimetric analysis curve of the sample of Example 5 of the present invention under a nitrogen atmosphere. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with examples. The specific examples described here are only used to explain the present invention and do not limit the present invention.
[0041] Embodiment 1:
[0042] (1) Take 10 g of lignin and add it to 50 mL of tetrahydrofuran solution, stir for 30 min to fully disperse it, then add 15 g of 50% phytic acid solution and 1 g of urea, and reflux at 70 °C for 8 h. After the reaction is completed, the product is centrifuged, washed with ethanol several times, and then vacuum dried at 60 °C for 12 h to obtain phosphated lignin (P-Lignin).
[0043] (2) Take 2g of the modified lignin prepared above and disperse it in deionized water, add 0.1g Cu(Ac) 2 ·H 2 O, stirred at 50 °C for 2 h, the product was centrifuged, washed with deionized water and ethanol respectively until the washing liquid was completely colorless, and dried to obtain the metal-modified phytic acid lignin carbonizing agent (P-Lignin@Cu).
[0044] The morphology of the product samples was characterized by scanning electron microscopy. Figure 1 The following are scanning electron micrographs of lignin (Lignin), phosphated lignin (P-Lignin), and metal-modified phytic acid-based lignin carbonizer (P-Lignin@Cu). The introduction of phytic acid and metal has a great influence on the surface morphology of lignin. Since the abundant hydroxyl groups in phytic acid are conducive to the formation of stable hydrogen bonds, the surface of P-Lignin is quite smooth compared with lignin. In addition, the multi-coordination sites in phytic acid make the Cu ions in a highly coordinated state, and the particle size and morphology of P-Lignin@Cu change significantly, which is conducive to exposing more active sites.
[0045] The thermal stability of the product was analyzed by thermogravimetric analyzer. Figure 2 The mass loss curves and derivative mass curves of lignin (Lignin), phosphated lignin (P-Lignin) and metal-modified phytate-based lignin carbonizer (P-Lignin@Cu) are shown respectively. The catalytic degradation of Cu ions leads to a decrease in the thermal stability of P-Lignin@Cu, but also promotes the rapid formation of the carbon layer, which ultimately leads to an increase in the residual carbon content. Compared with pure lignin, the incorporation of phytic acid and Cu ions increases the yield of carbon residue from 10.07wt% to 34.22wt%. Due to the complex composition of lignin, including Cα-Cβ-Cγ side chains and abundant functional groups on the aromatic rings, the pyrolysis occurs in a wide temperature range, from room temperature to about 600℃. The derivative thermogravimetric curve of lignin has two representative rapid decomposition stages, corresponding to the decomposition of the CC main chain and β-β structure, respectively. Surface modification changes the degradation behavior of lignin. The catalysis of transition metal Cu makes lignin almost completely pyrolyzed before 350°C. Cu accelerates the reaction between phosphoric acid and lignin matrix, making it dehydrated into carbon faster and increasing the formation of carbon layer.
[0046] Embodiment 2:
[0047] First, the dried pine needles were crushed, and then 9 g of pine needle powder and 1 g of ammonium polyphosphate were weighed and uniformly mixed to obtain a composite powder (PN / APP 10) with an ammonium polyphosphate loading of 10 wt%.
[0048] Embodiment 3:
[0049] First, 4 g of ammonium polyphosphate and 1 g of the copper-based phytic acid modified lignin carbonizing agent prepared above were weighed and mixed evenly to obtain a composite fire retardant powder. Then, the dried pine needles were crushed, and 9 g of pine needle powder and 1 g of the composite fire retardant were weighed and mixed evenly to obtain a composite powder (PN / APL@Cu 10) with a fire retardant loading of 10 wt%.
[0050] Embodiment 4:
[0051] First, 4 g of ammonium polyphosphate and 1 g of the copper-based phytic acid modified lignin carbonizing agent prepared above were weighed and mixed evenly to obtain a composite fire retardant powder. Then, the dried pine needles were crushed, and 8 g of pine needle powder and 2 g of the composite fire retardant were weighed and mixed evenly to obtain a composite powder (PN / APL@Cu 20) with a fire retardant loading of 20 wt%.
[0052] Embodiment 5:
[0053] First, 4 g of ammonium polyphosphate and 1 g of the copper-based phytic acid modified lignin carbonizing agent prepared above were weighed and mixed evenly to obtain a composite fire retardant powder. Then, the dried pine needles were crushed, and 7 g of pine needle powder and 3 g of the composite fire retardant were weighed and mixed evenly to obtain a composite powder (PN / APL@Cu 30) with a fire retardant loading of 30 wt%.
[0054] The above materials were analyzed by cone calorimeter, and pure pine needles (Pure PN) were used as a comparison. The results are referenced Figure 3 , Figure 4 and Figure 5 . Figure 3 This is a heat release rate diagram of the composite material provided in Examples 2 to 5 of the present invention. Since Lewis acid coordination has a certain effect on the vegetation segment and can quickly catalyze the degradation of the segment, the peak heat release rate increases slightly after the copper-based phytic acid carbonizing agent replaces part of the ammonium polyphosphate, but the flame burning time is also greatly reduced. Figure 4 The total heat release diagram of the composite material provided in Examples 2-5 of the present invention further verifies that the carbon-forming agent can rapidly form carbon by promoting the degradation of fragments, thereby reducing the continuous release of heat. In addition, Figure 5 From the total smoke release diagram of the composite materials provided in Examples 2-5 of the present invention, it can be seen that the copper-based carbonizing agent also has good smoke suppression performance through the catalytic carbonization effect.
[0055] Embodiment 6:
[0056] According to 0.6kg / m 2 The load was evenly spread on a 120×50 cm test bench. A thermocouple was set every 15 cm from five centimeters (5, 20, 35, 50, 65, 80, 95, 110 cm). The barrier was set at 65-85 cm. A heat flux meter was set in the center of the barrier to record the radiation heat flux. Ammonium polyphosphate and copper-based phytic acid-modified lignin carbonizing agent were compounded in a ratio of 4:1 and sprayed on the barrier by a peristaltic pump. After the heat source was dried, an ignition experiment was performed. A cotton thread soaked in ethanol was set at the beginning of the test bench to ensure that the flame spread in a straight line.
[0057] Weigh 360g of pine needles and spread them evenly on the test bench. Then weigh 4g of ammonium polyphosphate and 1g of copper-based phytic acid modified lignin carbonizing agent to make a powder and dissolve it in water. Use a peristaltic pump to spray it on the surface of the pine needles in an area of 20×50cm. After drying with a heat source, conduct an ignition experiment.
[0058] Embodiment 7:
[0059] 360g of pine needles were weighed and evenly spread on the test bench. Then 8g of ammonium polyphosphate and 2g of copper-based phytic acid modified lignin carbonizing agent were weighed and mixed into powder and dissolved in water. The powder was sprayed on the surface of the pine needles with a peristaltic pump in an area of 20×50cm. After drying with a heat source, an ignition experiment was carried out.
[0060] Embodiment 8:
[0061] Weigh 360g of pine needles and spread them evenly on the test bench. Then weigh 10g of ammonium polyphosphate powder and dissolve it in water. Use a peristaltic pump to spray it on the surface of the pine needles in an area of 20×50cm. After drying with a heat source, conduct an ignition experiment.
[0062] The samples sprayed with the barrier tape were compared with pure pine needles (Pure PN) for fire spread test. The temperature changes during the fire spread process provided in Examples 6-8 are as follows: Figure 6 , Figure 7 , Figure 8 and Fig. 9 It is obvious that compared with Figure 6 Pure pine needles, Figure 7 According to 50g / m 2 After the barrier belt was laid with ammonium polyphosphate and copper-based phytic acid modified carbonizing agent, the temperature of the thermocouple inside the barrier belt dropped significantly. When the spraying dosage increased to 100g / m 2 When the flame front reaches the fifth thermocouple, it stops spreading, confirming the effectiveness of the carbonizing agent. Fig. 9 Compared with 100g / m 2 The flame suppression effect of the barrier zone with only ammonium polyphosphate added is very good. Since ammonium polyphosphate itself cannot form an effective carbon layer, it is almost impossible to prevent the spread of flames, which further verifies the high efficiency of the copper-based phytic acid modified carbonizing agent.
[0063] The above description is only an embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be within the scope of protection of the present invention.
Claims
1. A method for preparing a bio-based phytate efficient carbon-forming agent, characterized in that The steps include: Step 1: Disperse lignin in a solvent, stir and disperse it evenly, then add phytic acid solution, then add urea as a reaction catalyst, heat to reflux for esterification reaction; after the reaction is completed, centrifuge and wash the product to remove unreacted products, and dry it to obtain phytic acid-modified phospholipid lignin; Step 2: The phytic acid-modified phospholipid lignin obtained in step 1 is dispersed in a solvent, a copper salt aqueous solution is added dropwise under heating, magnetic stirring is performed, and centrifugal washing is performed to obtain a bio-based phytate high-efficiency carbonizing agent.
2. The preparation method according to claim 1, characterized in that: In step 1, the mass ratio of lignin to phytic acid solution is 2:3-4, and urea accounts for 10-25wt% of lignin.
3. The preparation method according to claim 1, characterized in that: In step 1, the heating reaction temperature is 70° C. and the reaction time is 8 h.
4. The preparation method according to claim 1, characterized in that: In step 2, the copper salt is copper acetate.
5. The preparation method according to claim 1, characterized in that: In step 2, the mass ratio of phytic acid-modified phospholipid lignin and copper salt is 1:0.025~0.
25.
6. The preparation method according to claim 1, characterized in that: In step 2, the heating temperature is 50° C. and the reaction time is 2 h.
7. A bio-based phytate efficient carbon-forming agent, prepared according to any one of the preparation methods of claims 1-6.
8. The use of the bio-based phytate efficient carbon-forming agent according to claim 7 in constructing a fire barrier belt, characterized in that: The bio-based phytate high-efficiency carbon-forming agent and ammonium polyphosphate are compounded and added to a vegetation firebreak.
9. The use according to claim 8, characterized in that: The mass ratio of the carbon-forming agent to ammonium polyphosphate is 1:1-7.
10. The use according to claim 9, characterized in that: The total spraying amount of the carbon forming agent and ammonium polyphosphate is ≥100g / m 2 .
Citation Information
Patent Citations
Modified lignin, preparation method and application of modified lignin in toughening flame-retardant composite material
CN111848977A
Intumescent flame retardant, preparation method and application of intumescent flame retardant, flame-retardant polyacrylonitrile fiber and preparation method of flame-retardant polyacrylonitrile fiber
CN114437366A
Phytic acid supramolecular flame retardant, preparation method and application
CN114773615A
Flame-retardant polyurethane cable outer sheath material
CN116478527A
Water-based flame-retardant fire extinguishing agent as well as preparation method and application thereof
CN116672646A
Cited By
Flame retardant and flame-retardant coating for transparent wood, preparation method of flame retardant and flame-retardant coating, and fireproof transparent wood
CN121268035A